ChemInform Abstract: Direct Hydrofluorothermal Synthesis of Sodium Transition Metal Fluorosulfates as Possible Na‐Ion Battery Cathode Materials. Issue 21 (2nd May 2013) - Wang, Qianlong; Madsen, Alex; Owen, John R.; Weller, Mark T.
Abstract The isomorphous compounds (IIIa—c) crystallize in the orthorhombic space group Pbcn with Z = 4 (single crystal XRD).